2009
DOI: 10.1063/1.3103486
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop learning control of isomerization using shaped ultrafast laser pulses in the deep ultraviolet

Abstract: We demonstrate the use of shaped ultrafast laser pulses in the deep ultraviolet to control the ring opening isomerization of 1,3-cyclohexadiene to form 1,3,5-hexatriene. The experiments are performed with a gas phase sample and the isomerization yield is probed with dissociative ionization driven by a time-delayed, intense infrared laser pulse. Differences in the electronic structure of the ions for the two isomers, as shown by ab initio calculations, result in very different fragmentation products following s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 34 publications
(32 reference statements)
2
68
0
Order By: Relevance
“…This process has been extensively studied, in part because of its role in vitamin D biosynthesis. Time-resolved pump-probe techniques have been employed to understand this process [20][21][22][23][24][25]. These studies have found that the conical intersection-mediated ring-opening step in isomerization is completed in less than 200 fs [22], after which the molecule undergoes conformational changes on a range of timescales (see inset in Fig.…”
mentioning
confidence: 99%
“…This process has been extensively studied, in part because of its role in vitamin D biosynthesis. Time-resolved pump-probe techniques have been employed to understand this process [20][21][22][23][24][25]. These studies have found that the conical intersection-mediated ring-opening step in isomerization is completed in less than 200 fs [22], after which the molecule undergoes conformational changes on a range of timescales (see inset in Fig.…”
mentioning
confidence: 99%
“…Linear interpolations in internal coordinates at the SA4-CASSCF level were used to connect cis,cis-COD to the two CIs found, and the CIs to the products. The conical intersection for CHD is taken from previous work [7]. Linear interpolations between CHD and the CI and HT and the CI were computed using CASSCF(6,6) with the cc-pVDZ basis set and averaging 3 states.…”
Section: Methodsmentioning
confidence: 99%
“…We consider the ionization of 1,3-cyclohexadiene (CHD), whose ionization potential is slightly above our photon energy of 7.94 eV. The excited state dynamics of CHD has been the subject of intense study, [3][4][5][6][7], and it's neutral excited state dynamics are well understood. Initial excitation to the first bright state (S 1 ) is followed by rapid internal conversion to the ground states, with some fraction of the molecules isomerizing to form 1,3,5-hexatriene (HT).…”
Section: Introductionmentioning
confidence: 99%
“…However, in all cases this angle is small enough to justify the simplifications used in Eq. (12). Using this replacement, the interaction Hamiltonian becomes,…”
Section: A Lg-molecule Interaction Hamiltonianmentioning
confidence: 99%
“…While many researchers have investigated how changes to the spectrum of an ultrashort pulse of light can control atomic and molecular dynamics, few researchers have looked into the ability of light fields, continuous or pulsed, * arury@caltech.edu to affect the fundamental coupling of nuclear and electronic degrees of freedom that determine subsequent dynamics and behavior. [6][7][8][9][10][11][12] However, recent studies propose the possibility that tailored transverse modes of light beams control the coupling of internal degrees of freedom of a molecule. [13,14] One such tailored optical mode is a Laguerre-Guass beam.…”
Section: Introductionmentioning
confidence: 99%